Improvement of antibacterial and biocompatibility properties of electrospray biopolymer films by ZnO and MCM-41 - OKTAR, FAİK NÜZHET (SPRINGER, 2020)
This study aims the improvement of antibacterial and biocompatibility properties of electrospray ternary blends of chitosan/poly(ethylene glycol)/hyaluronic acid. It conserves microscale particle structure even after incorporating zinc oxide (ZnO), the zeolite Mobil Composition of Matter No. 41 (MCM41) and penicillin G during this technique. Three different electrospray (ESP) blend compositions (ESPI, ESPII and ESPIII) have been produced in order to improve both antibacterial activity against to bothgram-positive and gram-negativebacteria and biocompatibility. Results of FTIR spectroscopy and microscopy verified with SEM, EDS and AFM analyses. Hyaluronic acid surface has been specified definitely through ZnO-based ESPI surface composed of heterogeneously dispersed microparticles. Surface structures of ESPII and ESPIII have more homogenously dispersed microparticles as hill-valley surface by the aid of MCM 41-PEN. Antibacterial activity has been performed by Kirby-Bauer method. ESPI has good antibacterial activity against both gram-positive (S. aureusandS. epidermidis) and gram-negative bacteria (E. cloacea). Each electrospray film displayed good biocompatibility against to mouse fibroblast cell line L929 (ATTC number CCL-1). The highest amount of cell proliferation has been detected on ESPIII surface.
Keywords: Electrospray; HA; ZnO; MCM 41; Microparticles; ZINC-OXIDE NANOPARTICLES; MESOPOROUS SILICA; DRUG-DELIVERY; CONTROLLED-RELEASE; PERFORMANCE; ACID